Analisis Dan Evaluasi Proses Bisnis Menggunakan Metode Failure Mode And Effect Analysis (Fmea) (Studi Pada Dinas Perpustakaan Dan Kearsipan Kota Batu) - Hisam Rahman Hakim; Aditya Rachmadi; Alfi Nur Rusydi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Office of Library and Archives of Batu City is an agency that has the main task and function of organizing public services in the field of literature and archives in the Batu City area. There are several problems that occur in the business processes that are carried out, especially in library services, such as getting complaints from library visitors, unfulfilled visitor requests and the loss of several collections of reading materials. Due to this, it is necessary to evaluate business processes to find out more about problems and find solutions. The initial step taken was to identify the ongoing business processes using the "Regulation of the Minister of State for the Empowerment of State Apparatus and Bureaucratic Reform Number 19 of 2018 concerning the Preparation of Business Process Map for Government Agencies" as a guide in identifying. Furthermore, modeling business processes using Business Process Modeling Notation (BPMN). The next stage is to analyze business processes using Failure Mode Effect Analysis (FMEA) to obtain potential problems with the highest RPN value and then formulate a recommended solution. The results of the formulation of recommendations for problem solutions are four types of information systems or IT infrastructure, namely Inventory Information Systems, integrated Online Service Calendar, Mail Information Systems, Digital Signature with IS / IT business benefits that can meet the principles of Responsiveness, Effectiveness and efficiency, Accountability and Transparency in Good governance.